Effectiveness of open source data loss prevention tool in cloud computing - Sulaiman, Mahathir (2013)
With the systems and applications migration from the traditional enterprise data center infrastructures to the virtualisation of cloud computing infrastructure, there are changes required in term of the way of system security and data security management. There are more various sources of threats to the data integrity preservation which may come from internal employees, external users, cloud providers and the vendor of cloud providers. Among the way to ensure the data is not leaked out is by looking at data loss prevention tool. The tool should be protecting data at all the three common states namely data in motion, data in transmit and data at rest. The thesis intention is to find out the effectiveness of using open source data loss prevention in cloud computing infrastructure. In addition, the thesis would also study the security vulnerabilities on the open source DLP deployment architecture system and propose the improved architecture setup. While the effectiveness evaluation is done using open source, there is also a need to find the market leading commercial data loss prevention tool and identified the market strength.